A Comparative Study of Early Childhood Teachers’ Digital Practices During and After COVID-19 - Tokić, Bernarda; Karamatić Brčić, Matilda; Miočić, Marijana (Revija za elementarno izobraževanje, 2025)
This study investigates early childhood teachers’ perceptions and use of digital media during and after the COVID-19 pandemic, addressing the need to understand evolving ICT practices in early education. Employing a longitudinal design, data were collected via structured questionnaires from the same kindergartens in 2020 and 2024. Quantitative analysis revealed stable self-assessed digital competence but changing pedagogical use and attitudes. The findings underscore the need for targeted digital training and systemic support. The study’s novelty lies in its comparative longitudinal approach, offering insight into the sustained impact of a global crisis on digital integration in early childhood education.